THE TECHNICAL AND ECONOMICAL PERFORMANCE OF THE âABCâ TYPE PADDY DRYER - ., Sutrisno; Wahyudin, M.; Ananto, E. Eko (Indonesian Journal of Agricultural Science, 2001)
Farmers in the villages always face the same problem of how to reduce the moisture content of paddy harvest during harvest and postharvest time, especially in wet season. At the farm level, the grain quality is poor and alternative drying using kerosene fuel is very costly. The objective of this research was to design and evaluate the technical and economicalÂ  performance of drying paddy using an equipment known as "ABC" dryer.Â  The dryer uses paddy husk as fuel. The research was conducted at Research Institute for Rice over three years (1993/94-1995/96). The result showed that the "ABC" type dryer could reduce the moisture content of 5 tons wet paddy from 22.25% to 15.03% in 9 hours or an average drying rate of 1.05% moisture content per hour, with drying cost of Rp 18kg-1. Reducing the moisture content further to 11.83% needed 16 hours or average drying rate 0.82% hour-1, with drying cost almost doubled (Rp 32 kg-1). These costs are far below that of kerosene drying, i.e., Rp 30 kg-1 and Rp 60 kg-1 to reach moisture content of 15.03% and 11.83%, respectively. Budget analysis showed that the B/C ratio were 1.57 and 1.84 and the IRR are above 41.26% and 47.42% to reach moisture contentsof 15.03% and 11.83%, respectively. The break even points of "ABC" dryer were 130 and 60 tons, respectively. The milling test showed that the milling rice from the "ABC" dryer had better recovery (milling rendement) and rice quality (head rice) was higher than that of from sun-drying.